Metode Dirosa sebagai Inovasi Pembelajaran Praktis Baca Al-Qur’an bagi Orang Dewasa di Desa Toddopulia, Kecamatan Tanralili, Kabupaten Maros,: The Dirosa Method as an Innovative Practical Approach to Quran Reading for Adults in Toddopulia Village, Tanralili Subdistrict, Maros Regency - Syamsiah Nur (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The DIROSA Program (Quran Education for Adults) is an innovative method for learning to read the Quran, implemented among adult women in Toddopulia Village. This method is specifically designed to address difficulties in learning to read the Quran through a practical, systematic, and engaging approach. The implementation of the program over 20 sessions showed significant results in improving participants' Quran reading skills. A total of 30 women participated in the program, with an attendance rate reaching 85%. Evaluation results indicated that 80% of participants improved their reading ability by two levels, and 85% were able to master correct letter articulation (makhraj). The program not only successfully enhanced participants' cognitive abilities but also revived their learning enthusiasm and strengthened social bonds among community members. The sustainability through Muslimah Wahdah Islamiyah Tanralili as the implementing partner, which will continue the mentoring on an ongoing basis.